Norway : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that Norway's real mainland GDP growth rebounded strongly in 2004, after a slowdown that began in late 2002. Very supportive monetary conditions, high oil prices, rising housing prices, strengthening consumer and business confidence, and an improved world economy contributed to the pickup in activity. The outlook for 2005 and 2006 is promising, with most of the factors that propelled the economy forward last year expected to continue into the near future.